Plasmonics for microwave photonics in the THz range - Burla, Maurizio; Hoessbacher, Claudia; Heni, Wolfgang; Haffner, Christian; Salamin, Yannick; Fedoryshyn, Yuriy; Watanabe, Tatsuhiko; Massler, Hermann; Blatter, Tobias; Horst, Yannik; Elder, Delwin L.; Dalton, Larry R.; et al. (Frontiers in Photonics, 2023)
THz frequencies offer enormous amounts of bandwidth, which could solve the current speed bottleneck for next-generation wireless communications. Recent reports show sub-THz links offering capacities of hundreds of Gbit/s, finally approaching those of state-of-the-art optical transmission channels. Nonetheless, generation, transport, detection and processing of signals in the THz range is far from being a trivial task. Even though the recent evolution of integrated technology is starting to indicate that chip-scale THz technology could gradually close the so-called “THz gap”, much work still needs to be done to enable functional systems, in particular in terms of efficiency. Photonics can be of help, thanks to its extremely low loss and broad bandwidth. Yet, a particularly critical aspect hindering the deployment of THz technology is that state-of-the-art photonics devices generally do not offer sufficient electro-optical bandwidth to process THz signals. Plasmonics, by focusing electromagnetic surface waves at sub-wavelength scales, can play a key role in this quest, as it finally enables the realization of electro-optical devices such as modulators and detectors displaying sufficient compactness and speeds to reach the THz range. This paper overviews recent achievements on plasmonic-based modulators displaying characteristics of speed, efficiency and linearity that enable high-performance access to this much desired frequency range.